From leaves to whole plants: positive effects of shelter‐builders on arthropod communities are stronger in dry seasons - Pereira, Cássio Cardoso; Fernandes, G. Wilson; Cornelissen, Tatiana (Biotropica, 2024)
Leaf shelters function as microclimatic refuges, reducing arthropod exposure to climatic fluctuations of surrounding habitats. Although facilitation is expected to increase under stressful conditions, empirical studies investigating the patterns of variation and magnitude of effects of ecosystem engineering (EE) at different spatial and temporal scales are still scarce. In this study, we evaluated the facilitation consequences of leaf shelter created by gall‐inducers on arthropod communities of Miconia ligustroides (DC.) Naudin (Melastomataceae). We evaluated how such effects change at the leaf and plant levels in a habitat subject to strong climatic seasonality. The presence of leaf shelters on M. ligustroides increased arthropod diversity and biomass, modified the species composition at both the leaf and plant levels, during wet and dry seasons. However, the addition of artificial leaf shelters during the dry season showed greater abundance, richness, and biomass of arthropods when compared to shelters added during the wet season. Regarding the global effects of artificial leaf shelters on the diversity of arthropods associated with M. ligustroides, the dry season showed strong and positive effects, increasing the abundance, richness, and biomass of arthropods by an average of 65% for both years. Our study contributes to a better understanding of the patterns of variation and magnitude of EE at different spatial and temporal scales and provides new insights into the importance of shelters for aridity‐sensitive species. In this study, we evaluated the facilitation consequences of leaf shelter created by gall‐inducers on arthropod communities of Miconia ligustroides (DC.) Naudin (Melastomataceae). We evaluated how such effects change at the leaf and plant levels in a habitat subject to strong climatic seasonality. The presence of leaf shelters on M. ligustroides increased arthropod diversity and biomass, modified the species composition at both the leaf and plant levels, during wet and dry seasons. However, the addition of artificial leaf shelters during the dry season showed greater abundance, richness, and biomass of arthropods when compared to shelters added during the wet season. Regarding the global effects of artificial leaf shelters on the diversity of arthropods associated with M. ligustroides, the dry season showed strong and positive effects, increasing the abundance, richness, and biomass of arthropods by an average of 65% for both years. Our study contributes to a better understanding of the patterns of variation and magnitude of EE at different spatial and temporal scales and provides new insights into the importance of shelters for aridity‐sensitive species.